2007
DOI: 10.1590/s0004-28032007000200002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência da infecção por Helicobacter pylori e das lesões precusoras do câncer gástrico em pacientes dispéticos

Abstract: RESUMO -Racional -A infecção pelo Helicobacter pylori é fator importante no desenvolvimento da carcinogênese gástrica, mas somente uma fração dos pacientes infectados irá desenvolver câncer gástrico. A infecção pelo H. pylori determina gastrite crônica não-atrófica, que pode evoluir para gastrite atrófica e metaplasia intestinal e, finalmente, para displasia e adenocarcinoma. , 3% e 15% das biopsias, respectivamente. A infecção por H. pylori determinou uma razão de chances 10 vezes (IC95% 6.50 -17%) maior de s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
6
0
4
Order By: Relevance
“…The incidence of gastric cancer was 2.9% in 1246 Japanese patients with H. pylori dyspepsia who were followed prospectively and no cases in 280 H. pylori-negative patients. Studies conducted by several researchers have demonstrated an association between H. pylori infection and gastric lesions as precursors of neoplasias [14]. In our research of 56 dyspeptic patients from the city of Nova Iguaçu, 12 (21.4%) were positive for H. pylori but in none of them malignant lesions were diagnosed.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The incidence of gastric cancer was 2.9% in 1246 Japanese patients with H. pylori dyspepsia who were followed prospectively and no cases in 280 H. pylori-negative patients. Studies conducted by several researchers have demonstrated an association between H. pylori infection and gastric lesions as precursors of neoplasias [14]. In our research of 56 dyspeptic patients from the city of Nova Iguaçu, 12 (21.4%) were positive for H. pylori but in none of them malignant lesions were diagnosed.…”
Section: Discussionmentioning
confidence: 59%
“…According to Parkin et al [13] and Mueller et al [14], gastric cancer is considered the second cause of cancer deaths in the world, and these authors considered that almost 2/3 of the these cases occur in developing countries. A significant advance in the etiology of gastric cancer was the identification of the H. pylori bacterium and its association with the gastric carcinogenesis process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these nitrous compounds and their metabolites are inhibited by vitamin C and other antioxidants agents that protect the DNA 4,21,23,27,29 . According to Muller et al (2007) the chronic atrophic gastritis, a potential late state of gastric infection by Helicobacter pylori (Hp), raises the risk of gastric cancer development up to six times 24 . Recently some clinical studies have related the prolonged use of PPI with the progressive worsening of gastritis in patients infected by Hp.…”
Section: Introductionmentioning
confidence: 99%
“…The infection by Helicobacter pylori has been the subject of investigation as a possible etiologic factor for ChU in the last few years (3,5,(7)(8)(9)(10)(11) . Helicobacter pillory affects nearly 50% of the world population (12) . In Brazil, its prevalence ranges from 34 to 80% adults and children (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pillory affects nearly 50% of the world population (12) . In Brazil, its prevalence ranges from 34 to 80% adults and children (12) . The prevalence is higher in childhood, mainly in low income regions (13) .…”
Section: Introductionmentioning
confidence: 99%